ANALISIS KOMPETENSI GURU DALAM PEMBELAJARAN ANGKLUNG MELALUI PENERAPAN METODE KODALY - Gemalia Rahmawati; Nandang Rusmana; Maulia Depriya Kembara; Udin Syaefudin Sa’ud; Atep Sujana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze teacher competence in angklung learning using the Kodaly method in formal education units. Kodaly's hand sign method, which converts musical notation into hand symbols, is applied to improve students' musical understanding and engagement in angklung learning. The research used the literature study method by reviewing various previous studies related to angklung music learning and teacher pedagogical competence. The results showed that the application of the Kodaly method was able to increase learning effectiveness, improve students' angklung playing skills, and create an interactive and fun learning atmosphere. This research emphasizes the importance of teacher competence, both in mastering music theory and teaching skills, to maximize student potential and preserve culture through angklung learning. In conclusion, the Kodaly method not only helps achieve learning objectives but also contributes to the preservation of traditional culture through fun and meaningful music teaching.